Trend of Mortality Due to Congenital Anomalies in Children Younger Than 5 Years in Eastern China, 2012-2021: Surveillance Data Analysis - Wen-Hong Dong; Jun-Xia Guo; Lei Wang; Shuang-Shuang Zheng; Bing-Quan Zhu; Jie Shao (JMIR Publications, 2024)
BackgroundAs one of the leading causes of child mortality, deaths due to congenital anomalies (CAs) have been a prominent obstacle to meet Sustainable Development Goal 3.2. ObjectiveWe conducted this study to understand the death burden and trend of under-5 CA mortality (CAMR) in Zhejiang, one of the provinces with the best medical services and public health foundations in Eastern China. MethodsWe used data retrieved from the under-5 mortality surveillance system in Zhejiang from 2012 to 2021. CAMR by sex, residence, and age group for each year was calculated and standardized according to 2020 National Population Census sex- and residence-specific live birth data in China. Poisson regression models were used to estimate the annual average change rate (AACR) of CAMR and to obtain the rate ratio between subgroups after adjusting for sex, residence, and age group when appropriate. ResultsFrom 2012 to 2021, a total of 1753 children died from CAs, and the standardized CAMR declined from 121.2 to 62.6 per 100,000 live births with an AACR of -9% (95% CI -10.7% to -7.2%; P<.001). The declining trend was also observed in female and male children, urban and rural children, and neonates and older infants, and the AACRs were -9.7%, -8.5%, -8.5%, -9.2%, -12%, and -6.3%, respectively (all P<.001). However, no significant reduction was observed in children aged 1-4 years (P=.22). Generally, the CAMR rate ratios for male versus female children, rural versus urban children, older infants versus neonates, and older children versus neonates were 1.18 (95% CI 1.08-1.30; P<.001), 1.20 (95% CI 1.08-1.32; P=.001), 0.66 (95% CI 0.59-0.73; P<.001), and 0.20 (95% CI 0.17-0.24; P<.001), respectively. Among all broad CA groups, circulatory system malformations, mainly deaths caused by congenital heart diseases, accounted for 49.4% (866/1753) of deaths and ranked first across all years, although it declined yearly with an AACR of -9.8% (P<.001). Deaths due to chromosomal abnormalities tended to grow in recent years, although the AACR was not significant (P=.90). ConclusionsCAMR reduced annually, with cardiovascular malformations ranking first across all years in Zhejiang, China. Future research and practices should focus more on the prevention, early detection, long-term management of CAs and comprehensive support for families with children with CAs to improve their survival chances.